(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2007)
A case of a 78-year-old female is reported, who died from bleeding caused by a small incised cutting wound, located on the right leg and affecting the fibular artery. Some 6 to 7 hours passed after the wound was caused and, all through this time she did several things, among them asking for help. Some first aid knowledge would probably avoid such deaths.